ANALYSIS AND GENERALIZATION OF GEOLOGICAL AND GEOPHYSICAL MATERIALS ON AGINSKY BLOCK (EAST AITUZ SQUARE) GEOLOGICAL AND GEOPHYSICAL STUDY - Yulchiboev Khusan Mirzokhidjon ugli; Abdullayev Dostonbek Akmal ugli; Saparov Diyorbek Dilshod ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The geological and geophysical study of the Ustyurt Plateau began in the 1950s, focusing on understanding the geological structure of the region and exploring for valuable resources, particularly oil and gas. Geological investigations led to a detailed analysis of Neogene layers and the identification of several anticlinal structures. Geophysical studies were conducted using magnetic, gravimetric, electrical, and seismic methods, providing insights into the area's oil and gas potential. Notably, seismic research employed modern techniques such as Vertical Seismic Profiling (VSP) and Multi-Channel Offset Seismic (MOGT), facilitating in-depth investigations of the structures. As a result, promising areas for oil and gas exploration were identified and prepared for deep drilling operations.